A study of the electric response of He II at the excitation of second sound waves - Chagovets, Tymofiy V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We report an experimental investigation of the electric response of superfluid helium. Our results confirm the presence of electric potential that appears at the relative oscillatory motion of normal fluid and superfluid components in helium generated by the heater. The resonance of the electric potential was observed in the first four harmonics. A suggested method for the detection of the electric response allows the required resonance peak to be distinguished from spurious signals. Our results are in qualitative agreement with the data published by previous researchers. The reasons for the discrepancy in the measured values of the potential difference are discussed.